1996
DOI: 10.1002/elan.1140081209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HY‐zeolites on the performance of tyrosinase‐modified carbon paste electrodes

Abstract: The dependence of electrode response on additive properties in enzyme-modified carbon paste was studied. Four different HY-zeolite powders, dealuminated to different extents and characterized by both SiiAl ratio and hydrophilicity, were used as the carbon paste modifiers. The enzyme tyrosinase used in biosensors for the detection of catechol and other phenolic compounds was chosen as the model system for the construction of a composite carbon paste biosensor incorporating different HY-zeolites as additives. Ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…[8] We also showed that for mediated carbon paste glucose biosensor, contrary to what could be expected at first sight, the decrease in the activity was not related to a simple enzymatic deactivation, but was essentially due to the disappearance of the mediator, namely the ferrocene. [10] Similar results, for glucose response, were again obtained when zeolite and glucose oxidase were successively deposed on the surface of the platinum electrode of an amperometric oxygen detector, or when GOx was adsorbed beforehand on zeolite particles prior to deposition on the platinum electrode. The dispersion of zeolite within such a mediatorless modified carbon paste electrode, utilizing Rh-C particles, affects the detection of the liberated hydrogen peroxide resulting in enhancing sensitivity, extending linear range and increasing stability of the biosensor.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…[8] We also showed that for mediated carbon paste glucose biosensor, contrary to what could be expected at first sight, the decrease in the activity was not related to a simple enzymatic deactivation, but was essentially due to the disappearance of the mediator, namely the ferrocene. [10] Similar results, for glucose response, were again obtained when zeolite and glucose oxidase were successively deposed on the surface of the platinum electrode of an amperometric oxygen detector, or when GOx was adsorbed beforehand on zeolite particles prior to deposition on the platinum electrode. The dispersion of zeolite within such a mediatorless modified carbon paste electrode, utilizing Rh-C particles, affects the detection of the liberated hydrogen peroxide resulting in enhancing sensitivity, extending linear range and increasing stability of the biosensor.…”
Section: Introductionsupporting
confidence: 57%
“…Such a high hydrophilicity permits a higher oxido-reduction rates due to an easier ion exchange between the electro-active species and the solution or to a better penetration of the electrolyte support in depth of the electrode. [10,11,13] Differing from the results showed in Fig. The modification of carbon paste electrodes by these zeolites strongly affects their electrochemical behaviors which showed strong dependency on the amount of loaded zeolite and on the nature and concentration of chemicals here present, on the surface of the electrode, in the zeolite or in the solution.…”
Section: Resultsmentioning
confidence: 85%
“…Although studies of ZMEs focus mainly on preparation methods of the modi®ed electrode, electrochemical characterization of ion exchange and the electrode process, as well as discussion of electron transfer mechanism [3±11], a few articles have emerged on electroanalytical application of ZMEs [12±17]. In particular, substantial efforts have been devoted to the development of voltammetric biosensors based on ZMEs, such as dopamine or epinephrine [18], glucose [19], and phenols [20] biosensors. Zeolite is an interesting material for applications in electroanalytical chemistry; Rilison [21] and Walcarius [22] have recently published reviews of this area.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of zeolites have been used in their protonic form for the production of catechol and hydroquinone using chemical oxidants [7]. A zeolite/carbon paste mixture electrode was used as enzyme-modified electrode for phenol oxidation [8].…”
Section: Introductionmentioning
confidence: 99%